Estimation des stocks de bivalves en élevage et des épibiontes dans la lagune de Thau et modélisation de la dynamique des populations d'huîtres creuses (Crassostrea gigas, Thunberg) - Gangnery, Aline (1999)
In Thau Iagoon (Mediterranean Sea), shellfish are cultured in suspension. Molluscs are reared on ropes that are suspended on frames. Principal species concerned by breeding are Crassostrea gigas, Mytilus galloprovincialis and, in a less extent, Ostrea edulis. A new sampling method was developped to assess the total stock of cultured shellfish and was tested in July 1998 and April 1999. The total stock was found to be 19500 tons (± 1120 SE) in 1998 and 14100 tons (± 830 SE) in 1999, thus exhibiting temporal variations. Temporal differences in the total stock are mainly attributable to the breeding cycle but also to sorne exceptionnal events which occurred in Thau lageon in 1997 and 1998 (water anoxia, bacteriological crisis, bloom of toxic algae). In the same time, the biomass of biofouling on ropes was found to be around 9000 tons for the two sampling years. A mode! of population dynamics was developped for the oyster C. gigas to understand the stock variations over time. The model allows to derive accurate estimations of the stock and the production at any time. Parameters used in the model were determined by investigating breeding schedule and by analysing datas on growth and food available (chlorophylle a). Finally, the model is used to simulate the evolution of stock and production from April up to December 1999. Dans l'étang de Thau (Méditerranée), l'élevage conchylicole se fait en suspension. Les coquillages sont fixés sur des cordes, elles-mêmes suspendues à des tables d'élevage. Les principales espèces élevées sont Crassostrea gigas, Mytilus galloprovincialis et, dans une moindre mesure, Ostrea edulis. Une nouvelle méthode d'estimation des stocks a été mise au point et testée en juillet 1998 et avril 1999. Le stock total des bivalves en élevage est estimé à 19500 tonnes(± 1120 Ec.T.) en 1998 et 14100 tonnes(± 830 Ec.T.) en 1999, montrant l'existence de variations temporelles. Cette différence est essentiellement liée au cycle d'élevage des coquillages dans l'étang mais également à plusieurs évènements ...